SAE Technical Paper Series 2013
DOI: 10.4271/2013-01-2524
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Hydrogen Direct Injection for Internal Combustion Engines

Abstract: Hydrogen has been largely proposed as a possible fuel for internal combustion engines. The main advantage of burning hydrogen is the absence of carbon-based tailpipe emissions. Hydrogen's wide flammability also offers the advantage of very lean combustion and higher engine efficiency than conventional carbon-based fuels. In order to avoid abnormal combustion modes like pre-ignition and backfiring, as well as air displacement from hydrogen's large injected volume per cycle, direct injection of hydrogen after in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…In contrast, it has been shown that hydrogen DI can lead to the same, or even higher, volume-specific power than that of conventional gasoline engines [1]. Moreover, the degree of in-cylinder mixture homogeneity or stratification at the time of ignition can be attuned by various DI strategies [3][4][5]. Typically high pressures are applied for DI fuelling in order to achieve high fuel mass flow rate and consequently rapid fuel-air mixing, particularly with late injection strategies [1,[3][4][5].…”
Section: Gaseous Fuellingmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, it has been shown that hydrogen DI can lead to the same, or even higher, volume-specific power than that of conventional gasoline engines [1]. Moreover, the degree of in-cylinder mixture homogeneity or stratification at the time of ignition can be attuned by various DI strategies [3][4][5]. Typically high pressures are applied for DI fuelling in order to achieve high fuel mass flow rate and consequently rapid fuel-air mixing, particularly with late injection strategies [1,[3][4][5].…”
Section: Gaseous Fuellingmentioning
confidence: 99%
“…Direct injection (DI) of gaseous fuels into the engine cylinder after intake valve closure [1][2][3][4][5] is believed to be the most preferable fuelling approach for advanced gaseous-fuelled engines. This is because DI can overcome the volumetric efficiency losses that occur with port fuel injection [1][2][3].…”
Section: Gaseous Fuellingmentioning
confidence: 99%
See 2 more Smart Citations
“…Several experimental and computational studies have been conducted on the development of hydrogen-fuelled IC engines in the past 15 years [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Port fuel injection (PFI) [6][7][8][9][10][11][12] and in-cylinder Direct Injection (DI) [13][14][15][16][17][18][19][20][21][22] of hydrogen are the two typical options for hydrogen-fuelled IC engines. DI offers higher volumetric efficiency and eliminates abnormal combustion modes such as preignition and backfire.…”
Section: Hydrogen-fuelled Internal Combustion Enginesmentioning
confidence: 99%